Novel perfusion ex-vivo culture system enables physiological and pathological studies on porcine arteries. (14th October 2021) - Matos, R; Maselli, D; McVey, J; Campagnolo, P
Abstract: Introduction: Routine cardiovascular interventions such as cardiac bypass, balloon angioplasty and stenting provoke vascular activation and remodelling often leading to rehospitalization and further interventions. Conventional in vitro models fail to account for the complex vascular environment essential for vascular tissue fitness. Purpose: Our research aims to culture whole porcine arteries in using a novel cost efficient and versatile perfusion system (EasyFlow) and identify the contribution of adventitial progenitors to post-injury remodelling. Methods: EasyFlow insert was 3D printed to convert a conventional 50 ml centrifuge tube into a mini bioreactor. Porcine arteries were excised and cultured under constant pulsatile flow for up to 7 days. Injury was performed by balloon catheter at day 0. Tissues were evaluated by doppler ultrasound, immunofluorescence and confocal imaging and PCR, at different timepoints. Results: The EasyFlow adaptor takes advantage of 50 ml centrifuge tubes isolating reaction space from the environment and reducing the culture volume. The adaptability of the design facilitates the incubation of vessels of different size and origin while the self-contained perfusion allows parallel cultures and minimal media consumption. EasyFlow perfusion culture of porcine arteries preserves the endothelial coverage and the smooth muscle cell organisation, as compared to static culture. Gene expression analysis and immunofluorescence indicated an increased expression of platelet-derived growth factor receptor beta (PDGFRb) and a decrease in smooth muscle actin (SMA) in the static culture, compared to the perfusion. Furthermore, static culture showed an increased cellular activation in adventitia (proliferating cell nuclear antigen expression), as compared to perfused tissues. Balloon injury followed by flow culture recapitulated the early hallmarks of vascular remodelling, including intimal denudation indicated by loss of platelet endothelial cell adhesion molecule signal, smooth muscle cell disarray shown by loss of actin stress fibre organisation and activation in the media, as supported by confocal microscope and gene expression analysis, accompanied by significant morphological changes based on ultrasound imaging. Conclusion: This work lay the basis for future investigations into the pathological remodelling of blood vessels, by providing a robust and controlled culture system for the maintenance of porcine blood vessels in culture. FUNDunding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): University of Surrey